2023
DOI: 10.3389/fimmu.2022.1084101
|View full text |Cite
|
Sign up to set email alerts
|

Immune response following traumatic spinal cord injury: Pathophysiology and therapies

Abstract: Traumatic spinal cord injury (SCI) is a devastating condition that is often associated with significant loss of function and/or permanent disability. The pathophysiology of SCI is complex and occurs in two phases. First, the mechanical damage from the trauma causes immediate acute cell dysfunction and cell death. Then, secondary mechanisms of injury further propagate the cell dysfunction and cell death over the course of days, weeks, or even months. Among the secondary injury mechanisms, inflammation has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 361 publications
0
25
0
1
Order By: Relevance
“…SCI is a temporary or permanent injury to the spinal cord, accompanied by motor and neurological dysfunction 148,149 . SCI can be divided into primary and secondary injuries 150 . Among them, the causes and mechanisms of secondary injury are diverse, mainly involving microglial activation, reactive oxygen species release, and neuroinflammation 151 .…”
Section: The Putative Effects and Mechanisms Of Il‐38 Underpinning Cn...mentioning
confidence: 99%
See 1 more Smart Citation
“…SCI is a temporary or permanent injury to the spinal cord, accompanied by motor and neurological dysfunction 148,149 . SCI can be divided into primary and secondary injuries 150 . Among them, the causes and mechanisms of secondary injury are diverse, mainly involving microglial activation, reactive oxygen species release, and neuroinflammation 151 .…”
Section: The Putative Effects and Mechanisms Of Il‐38 Underpinning Cn...mentioning
confidence: 99%
“…148,149 SCI can be divided into primary and secondary injuries. 150 Among them, the causes and mechanisms of secondary injury are diverse, mainly involving microglial activation, reactive oxygen species release, and neuroinflammation. 151 Neuroinflammation is known to play an essential role in the pathological development of SCI.…”
Section: Il-38 and Spinal Cord Injurymentioning
confidence: 99%
“…Traumatic spinal cord injury (SCI) is a devastating condition that occurs when a mechanical force (primary injury) causes direct damage to the spinal cord tissue, resulting in secondary injury mechanisms that lead to irreversible neuronal death and, ultimately, various degrees of neurological impairment and paralysis (Ahuja et al, 2017). Secondary injury encompasses multiple processes, including disruption of the blood-brain barrier, local ischemia, axonal shearing, gliosis, and neuroinflammation (Anjum et al, 2020; Sterner and Sterner, 2022). In recent years, preclinical research advances have significantly contributed to elucidating the pathology driving secondary injury mechanisms and identifying potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a major medical condition worldwide, often resulting in motor dysfunction and chronic pain syndromes. , Approximately one million people worldwide have been reported to suffer from SCI-related disorders each year, with traumatic contusions being the most common. , Traumatic SCI includes primary injury and secondary injury . Many studies have reported that secondary injury is an important stage in the treatment of SCI. , Timely therapeutic intervention can inhibit the progression of secondary injury and have a significant impact on long-term neurological and functional recovery . The spinal cord microenvironment in the secondary injury phase produces large amounts of reactive oxygen species (ROS) (e.g., H 2 O 2 ). , The ROS cannot be metabolized in a timely manner and form accumulation, leading to local ischemia, hypoxia, and inflammatory cascade response .…”
Section: Introductionmentioning
confidence: 99%
“…5 Many studies have reported that secondary injury is an important stage in the treatment of SCI. 6,7 Timely therapeutic intervention can inhibit the progression of secondary injury and have a significant impact on long-term neurological and functional recovery. 8 The spinal cord microenvironment in the secondary injury phase produces large amounts of reactive oxygen species (ROS) (e.g., H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%